2020
DOI: 10.1055/a-1017-3288
|View full text |Cite|
|
Sign up to set email alerts
|

Giant Non-Functioning Pituitary Adenoma: Clinical Characteristics and Therapeutic Outcomes

Abstract: Background Giant pituitary adenoma (≥4 cm) is a rare tumor whose clinical features and prognosis are not well known. Aim To evaluate the clinical characteristics and therapeutic outcomes of giant non-functioning PA (gNFPA). Patients and Methods A retrospective multicenter study of gNFPA patients diagnosed in a 12-year period was performed. In each patient, clinical data and therapeutic outcomes were registered. Results Forty patients (24 men, age 54.2 ± 16.2 years) were studied. The maximum tumor diameter [med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…On the one hand, this value represents a quantification of the difficulty of total resection during transsphenoidal surgery. Patients with residual tumors have a greater risk of progression postoperatively according to previous studies ( 5 , 15 18 ). The relapse rate was higher after 10 years of follow-up than after only 5 years of follow-up in patients with a residual tumor.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…On the one hand, this value represents a quantification of the difficulty of total resection during transsphenoidal surgery. Patients with residual tumors have a greater risk of progression postoperatively according to previous studies ( 5 , 15 18 ). The relapse rate was higher after 10 years of follow-up than after only 5 years of follow-up in patients with a residual tumor.…”
Section: Discussionmentioning
confidence: 84%
“…NFPAs are benign intracranial tumors arising from adenohypophyseal cells. Patients usually visit the clinic much later than the time of disease onset, with symptoms caused by the compressed tissue surrounding the macroadenoma ( 1 , 5 ). Therefore, the treatment and prognostic factors for NFPAs should be taken seriously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been found that, at the time of presentation, approximately 73–93% of patients with macroprolactinoma had evidence of FSH and LH deficiencies [ 17 ]. Fallah et al [ 18 ] noted a rate of approximately 60% for gonadal hormone abnormalities in macroadenomas, while, in a study on non-functioning adenomas by Iglesias et al [ 19 ], it was found that the gonadal axis was most often affected by pituitary adenomas, with a rate of 62.5% of abnormalities. The effects of various types of saddle lesions on male gonadal function have been described [ 20 ].…”
Section: Pituitary Adenomas and Male Hypogonadismmentioning
confidence: 99%
“…The pituitary dysfunctions included gonadal dysfunction, thyrotropic dysfunction, and corticotropic dysfunction; the rate of dysfunction in these three axes varied depending on the tumor characteristics of the study population. For gonadal axis dysfunction, as judged by the hormone levels alone, the preoperative dysfunction rate was approximately 25%; studies by Fallah et al [ 18 ] and Iglesias et al [ 19 ] reported gonadal axis hormone abnormalities of 61.3% and 62.5%, respectively. After surgical interventions, more than 80% of the patients in these studies had their gonadal axis hormone levels restored to levels similar to those before surgery; however, the percentage of patients with worse function was significantly higher than the percentage of patients with elevated function [ 57 ].…”
Section: Changes In Male Gonadal Function After Treatment Of Pituitar...mentioning
confidence: 99%